Moment of truth for aspirin use in variant angina: a meta-analysis. (25th November 2020) - Sousa, J.P; Puga, L; Lopes, J; Saleiro, C; Gomes, R; Lourenco, C; Goncalves, L
Abstract: Background: Aspirin has been a mainstay of antiplatelet therapy for coronary artery disease (CAD). However, in the context of variant angina (VA), high-dose aspirin was reported to exacerbate coronary spasms. Consequently, the value of traditional low-dose aspirin in VA, especially if not associated with atherosclerotic CAD, may be disputed. Purpose: To perform a meta-analysis aimed at evaluating the extent to which low-dose aspirin therapy influences cardiovascular (CV) prognosis in VA. Methods: We systematically searched MEDLINE, Embase, Web of Science, Cochrane Library and Google Scholar for studies addressing the long-term impact of low-dose aspirin on main CV outcomes of VA patients, published up until February 1, 2020. The primary endpoint was all-cause mortality, whereas secondary endpoints included CV mortality, acute coronary syndrome (ACS) events, revascularization procedures and hospital admissions for angina. The subgroup of patients with no significant epicardial CAD was further investigated separately, underneath similar outcomes. Study-specific odds ratios (ORs) were pooled using traditional meta-analytic techniques, under a random-effects model. Results: One prospective multicenter and two retrospective single-center studies, encompassing 1652 and 1164 patients, respectively, were regarded as eligible for quantitative evaluation. Median follow-up ranged between 12 and 52.1 months. 1284 patients were allocated to the aspirin arm and 2770 had no epicardial CAD. Absolute number of events for each endpoint may be reported as follows: all-cause mortality, 33; CV mortality, 11; ACS, 57; revascularization, 14; hospital admission for angina, 218. Aspirin was not found to reduce neither all-cause mortality (OR 0.78, 95% CI 0.38–1.58, p=0.49, i2=0%), nor CV mortality (OR 0.98, 95% CI 0.30–3.25, p=0.98, i2=0%), nor ACS events (OR 1.44, 95% CI 0.51–4.10, p=0.49, i2=47%), nor revascularization procedures (OR 2.06, 95% CI 0.63–6.75, p=0.23, i2=0%), nor hospital admissions for angina (OR 1.60, 95% CI 0.67–3.80, p=0.29, i2=86%). Likewise, this comprehensively neutral effect held true in those with VA and no significant atherosclerotic CAD (OR 1.04, 95% CI 0.28–3.92, p=0.95, i2=0%, for CV mortality; OR 1.29, 95% CI 0.19–8.94, p=0.79, i2=33%, for revascularization; OR 1.73, 95% CI 0.81–3.73, p=0.16, i2=75%, for hospital admission for angina). Conclusion: Even though scarce, currently available evidence suggests that low-dose aspirin is not effective in shrinking major adverse cardiovascular events in VA patients, particularly in those with no epicardial CAD. On the other hand, lower doses of aspirin may avoid the menace of clinically significant coronary spasms. Funding Acknowledgement: Type of funding source: None